Identifying Students’ Problems on Critical Thinking as a Way to Foster Higher Order Thinking Skills - Andi Dian Rahmawan; Eko Perianto (Pioneer: Journal of Language and Literature, 2021)
Students in the old days were not taught to think for themselves in a logical, systematic, and coherent way. They simply regurgitated lectures and text materials back to the teachers. Integrating the traditional method of teaching with the critical thinking model would be the better alternative for teachers to prepare students to solve problems in the future. The samples of this study are the whole graduated students from English Department Students at University of PGRI Yogyakarta, starting from 2018-2021. It is descriptive qualitative research, focusing on the assessment matrix in the assessment of thesis examination by giving in-depth highlight on trends. From the data analyses, it is inferred that gender would give less impact to the successfulness of developing Critical Thinking. On the other hand, the autonomous learning would never give the same good results from one condition to another. It is revealed from the finding that learning with peers impacts better than the autonomous learning and learning with teachers.